Parazoanthus Haddon & Shackleton, 1891, and Parazoanthidae Delage & Hérouard, 1901: Conservation of usage by Reversal of Precedence with Bergia Duchassaing & Michelotti, 1860, and Bergiidae Verrill, 1869 (Cnidaria: Anthozoa: Hexacorallia) - Low, Martyn E. Y.; Reimer, James Davis (Zootaxa, 2011)
The names Bergia Duchassaing & Michelotti, 1860, and Bergiidae Verrill, 1869, are respectively, senior subjective synonyms of Parazoanthus Haddon & Shackleton, 1891, and Parazoanthidae Delage & Hérouard, 1901. The junior synonyms Parazoanthus and Parazoanthidae are in current and widespread use. In the interest of nomenclatural stability, we enact Articles 23.9.1 and 23.9.2 to reverse precedence of these names, thereby making Parazoanthus and Parazoanthidae nomina protecta, and Bergia and Bergiidae nomina oblita.